THE BEST LABORATORY WORK TYPE TO IMPROVE HIGHER ORDER THINKING SKILLS AND SCIENTIFIC ATTITUDE - Adi Pramuda; Lia Angraeni; Soka Hadiati; Mislan Sasono (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2022)
This study aims to determine the effectiveness of the comprehensive laboratory work (lab work) type which is the combinations of deductive, problem solving, and technical skills type in increasing the higher-order thinking skills (HOTS) and scientific attitudes as well as empirical testing the compatibility of this comprehensive type against higher HOTS and scientific attitudes. The study involved 100 students’ level two physics majors consisting of 4 randomly selected classes with cluster random sampling techniques. Scientific attitudes are measured by the scale of attitudes including indicators of curiosity, critical attitudes, and cooperation. HOTS are measured by tests that include analytical, evaluation and creating skills. This study is experimental research with the randomized Solomon four-group design. The effectiveness test of the comprehensive laboratory type in this study using the Nonparametric Kruskal Wallis test. Model match analysis is performed with the structural equation model (SEM). The results showed that there were significant differences in HOTS and scientific attitude score after the application of the comprehensive lab work type. The average student score taught with the comprehensive laboratory type is higher than that of students taught with the deductive type.